Dental and Orthopaedic Implant Loosening: Overlap in Gene Expression Regulation - Schluessel, Sabine; Hartmann, Eliza S.; Koehler, Miriam I.; Beck, Felicitas; Redeker, Julia I.; Saller, Maximilian M.; Akova, Elif; Krebs, Stefan; Holzapfel, Boris M.; Mayer-Wagner, Susanne (Frontiers in Immunology, 2022)
Objectives: Endoprosthetic loosening still plays a major role in orthopaedic and dental surgery and includes various cellular immune processes within peri-implant tissues. Although the dental and orthopaedic processes vary in certain parts, the clinical question arises whether there are common immune regulators of implant loosening. Analyzing the key gene expressions common to both processes reveals the mechanisms of osteoclastogenesis within periprosthetic tissues of orthopaedic and dental origin. Methods: Donor peripheral blood mononuclear cells (PBMCs) and intraoperatively obtained periprosthetic fibroblast-like cells (PPFs) were (co-)cultured with (± macrophage-colony stimulating factor (MCSF) and Receptor Activator of NF-κB ligand (RANKL)) in transwell and monolayer culture systems and examined for osteoclastogenic regulations (MCSF, RANKL, osteoprotegerin (OPG), and tumor necrosis factor alpha (TNFα)) as well as the ability of bone resorption. Sequencing analysis compared dental and orthopaedic (co-)cultures. Results: Monolayer co-cultures of both origins expressed high levels of OPG, resulting in inhibition of osteolysis shown by resorption assay on dentin. The high OPG-expression, low RANKL/OPG ratios and a resulting inhibition of osteolysis were displayed by dental and orthopaedic PPFs in monolayer even in the presence of MCSF and RANKL, acting as osteoprotective and immunoregulatory cells. The osteoprotective function was only observed in monolayer cultures of dental and orthopaedic periprosthetic cells and downregulated in the transwell system. In transwell co-cultures of PBMCs/PPFs profound changes of gene expression, with a significant decrease of OPG (20-fold dental versus 100 fold orthopaedic), were identified. Within transwell cultures, which offer more in vivo like conditions, RANKL/OPG ratios displayed similar high levels to the original periprosthetic tissue. For dental and orthopaedic implant loosening, overlapping findings in principal component and heatmap analysis were identified. Conclusions: Thus, periprosthetic osteoclastogenesis may be a correlating immune process in orthopaedic and dental implant failure leading to comparable reactions with regard to osteoclast formation. The transwell cultures system may provide an in vivo like model for the exploration of orthopaedic and dental implant loosening.